A description of two new species of the genus Erenna (Siphonophora: Physonectae: Erennidae), with notes on recently collected specimens of other Erenna species - Pugh, P.r.; Haddock, S.h.d. (Zootaxa, 2016)
Two new Erenna species, E. insidiator sp. nov. and E. sirena sp. nov., are described from specimens collected in the vicinity of Monterey Bay, California, and also, for E. sirena at the southern end of the Gulf of California, Mexico. Further information on the three extant Erenna species is given, based on specimens collected in the same areas. These have enabled, for instance, the identification of three types of tentilla on the tentacles of E. cornuta Pugh, 2001, rather than the two noted on the single previously known specimen. The genus is remarkable for the presence of bioluminescent lures on the tentilla of all five species. In E. sirena sp. nov. the tentilla are also covered by a red-fluorescent layer, which was briefly described by Haddock et al. (2005), and further details are given herein. Another extraordinary feature of the colonies E. sirena sp. nov. is that the main part of the tentacle, with its tentilla, can be extended away from the siphosomal stem on a long peduncle. This phenomenon also appears to occur in E. laciniata Pugh, 2001, and has not been observed before for other physonect species.